Why should we teach about the Holocaust? - Ambrosewicz-Jacobs, Jolanta, 1957- 1957- (Judaica Foundation - Center for Jewish Culture, 2004)
Collection of first-hand accounts of Holocaust survivors, teachers, administrators and polticicans.